Bio-based flame-retardant coating based on ammonium polyphosphate as well as preparation method and application of bio-based flame-retardant coating
By using chitosan, lignin and ammonium polyphosphate to prepare bio-based flame retardants, the problems of halogen content and excessive addition amount in existing flame retardants were solved, and efficient and environmentally friendly flame retardant effect was achieved. The limit oxygen index reached 32.6% and passed the UL-94V-0 grade test.
Patent Information
- Application Number
- CN202510056420.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-14
- Publication Date
- 2025-04-22
- Estimated Expiration
- 2045-01-14
AI Technical Summary
The existing flame retardants contain halogen, which leads to environmental pollution and excessive addition, resulting in high production costs.
Chitosan, lignin and ammonium polyphosphate are used as the main raw materials, and through the acid source as the source of acid and carbon and gas, the dehydration and carbonization of the material are promoted, the dense carbon layer is formed, and the limit oxygen index is improved, thereby improving the flame retardant effect of the material.
Halogen-free bio-based flame retardant is achieved, reducing raw material costs, improving flame retardant performance, with an ultimate oxygen index of 32.6%, and passed the UL-94V-0 grade test.
Smart Images

Figure CN119859447A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of flame retardant materials, and in particular to a bio-based flame retardant coating based on ammonium polyphosphate and a preparation method and application thereof. Background Art
[0002] Wood is a commonly used renewable natural polymer material with the characteristics of rich raw materials and low cost. However, the flammable properties of wood require a flame retardant layer to be constructed on the surface of the wood to meet the application requirements. Lignin, as a common biomass material, has a large number of phenolic hydroxyl groups, which form a protective carbon layer during combustion and reduce the flammability of the polymer. Therefore, a bio-based flame retardant can be prepared. For example, existing document 1 ("Hexachlorocyclotriphosphazenefunctionalized lignin as a sustainable and effective flame retardant forepoxy resins[J]".Industrial Crops and Products, 2022, 187:115543.) uses hexachlorocyclotriphosphazene to modify lignin as an additive to improve the flame retardancy of epoxy resin. This technical solution requires the addition of 20wt.% functionalized lignin to enable the epoxy resin composite material to obtain a limiting oxygen index of 28.2%, and achieve the technical effect of UL-94V-0 grade in the vertical burning test. There are two main problems with this technical solution: 1. The additive contains chlorine, which is a halogen flame retardant. During combustion, harmful gas hydrogen chloride is released, causing environmental pollution; 2. The amount of flame retardant added is too high, resulting in high production costs and large processing.
[0003] In order to solve the problem of halogen-containing and excessive addition in the above-mentioned flame retardants, bio-based flame retardants can be prepared by introducing biomass containing N and P elements. For example, existing document 2 (Flame retardant polypropylene with a single molecule intumescent flame retardant based on chitosan [J]. Materials Today Communications, 2022, 33: 104689.) Melamine formaldehyde resin is coated with chitosan and ammonium polyphosphate by in-situ polymerization to modify polypropylene. Chitosan single molecule intumescent flame retardant inhibits thermal degradation of polypropylene and promotes the formation of a carbon layer. Although this technical solution realizes halogen-free bio-based flame retardant and improves thermal stability, the limiting oxygen index is only 25.7%, and vertical combustion can only reach UL-94V-1 level. The reason is that the gas generated by the gas source cannot expand effectively, resulting in the inability to form a dense carbon layer, which causes the carbon layer structure formed by chitosan to be easily destroyed, that is, a stable carbon layer cannot be formed.
[0004] In order to improve the compactness of the residual carbon layer and the limiting oxygen index, thereby improving the integrity and flame retardant properties of the carbon layer, the inventor's research group conducted preliminary work, and the existing document 3 ("A flame retardant coating based on PA-MEL flame retardant curing agent and its preparation method and application" CN202410058920.2) used phytic acid-melamine polyelectrolyte PM as a bio-based flame retardant curing agent for sodium lignin sulfonate modified urea-formaldehyde resin. When the addition amount of PM is only 2wt.%, a continuous and dense residual carbon layer can be obtained, and the limiting oxygen index of the wood after coating the flame retardant coating reaches 32.1%, and at the same time, the UL-94 grade reaches V-0 grade.
[0005] In addition, another preliminary work of the research group of the inventor of the present invention, existing document 4 ("A urea-formaldehyde resin blended guanazole-phytic acid-copper flame retardant resin coating and its preparation method and application" CN202411322652.7) uses guanazole, phytic acid and copper source as bio-based flame retardant and blends them with urea-formaldehyde resin for wood flame retardancy. When the addition amount is only 1wt.%, the residual carbon layer is continuous and dense. After coating the flame retardant coating, the wood reaches UL-94V-0 grade and LOI reaches 32.0%.
[0006] Both of the above technical solutions use phytic acid, a bio-based flame retardant material, as a phosphorus source. Although phytic acid has the advantages of being environmentally friendly and non-toxic, such phytic acid-based flame retardants all have the problem of low decomposition temperature. In addition, phytic acid is a soluble weak acid. On the one hand, due to its solubility, it has the problem of reduced flame retardant effect in a hot and humid environment. On the other hand, the acidity has a corrosive effect on wood and other components. In addition, although the existing document 4 uses metal copper to catalyze the degradation of resin to form a dense residual carbon layer and improve the flame retardant properties of the material, there are still problems of heavy metal pollution and recycling after disposal. Summary of the invention
[0007] The purpose of the present invention is to provide a bio-based flame retardant coating based on ammonium polyphosphate and a preparation method and application thereof. Aiming at the problems existing in the prior art, the bio-based flame retardant coating is prepared by introducing chitosan, lignin and ammonium polyphosphate as main raw materials.
[0008] in,
[0009] Ammonium polyphosphate is used as the acid source, which works synergistically with the carbon source and gas source to promote the dehydration and carbonization of the material, form a dense carbon layer, and increase the limiting oxygen index, thereby improving the flame retardant effect of the material and reducing the cost of raw materials;
[0010] Chitosan is used as a carbon source and a nitrogen source, and is dehydrated and condensed with chain polymer ammonium polyphosphate as a phosphorus source under acidic conditions;
[0011] The molecular structure of urea-formaldehyde resin is modified by melamine to improve the aging resistance of the resin, enhance the bonding performance of the resin, and improve the bonding performance with wood. In addition, melamine can also improve the thermal stability of urea-formaldehyde resin, and produce a stable carbon layer and release non-flammable gas nitrogen when decomposed at high temperature, which slows down the combustion speed;
[0012] Tannic acid is used as a curing agent to maintain the original color of the wood and reduce resin cracking;
[0013] Dioctyl phthalate (DOP) is used as a plasticizer to improve the mechanical properties of the flame retardant.
[0014] In order to achieve the above invention object, the technical solution adopted by the present invention is:
[0015] A bio-based flame retardant coating based on ammonium polyphosphate, which is prepared by using chitosan / lignin / ammonium polyphosphate bio-based flame retardant CS / LS / APP, referred to as CLA, as a flame retardant, urea, formaldehyde and melamine as resin raw materials, dioctyl phthalate DOP as a plasticizer, and tannic acid as a curing agent;
[0016] The CLA is prepared from lignin LS, chitosan CS and ammonium polyphosphate APP. CLA contains -NH2, OH, P=O, PO -, -CONH2;
[0017] The temperature at which the decomposition mass of the obtained CLA reached 5% was 228.63±5°C, and the temperature at which the maximum decomposition rate was reached was 295.4±5°C; the residual carbon content at 800°C was 24.29±2wt.%.
[0018] A method for preparing a bio-based flame retardant coating based on ammonium polyphosphate comprises the following steps:
[0019] Step 1, preparation of chitosan / lignin / ammonium polyphosphate bio-based flame retardant CLA, first, lignin LS, chitosan CS and ammonium polyphosphate APP meet a certain mass ratio, prepare LS solution, CS solution and APP solution respectively, then, under certain dropping conditions, add the LS solution dropwise into the CS solution to react to obtain a LS / CS mixed solution, finally, under the same dropping conditions, add the APP solution dropwise into the LS / CS mixed solution to react, and obtain chitosan / lignin / ammonium polyphosphate bio-based flame retardant CS / LS / APP, referred to as CLA;
[0020] In the step 1, the mass ratio of LS, CS and APP is 2:2:1;
[0021] In the step 1, the preparation method of the LS solution is to place LS in deionized water for stirring and dissolving at a dissolving temperature of 30° C., a dissolving stirring speed of 400-450 rpm, and a dissolving stirring time of 30 min to obtain a LS solution;
[0022] In the step 1, the CS solution is prepared by dissolving CS in a lactic acid solution and stirring and dissolving the CS solution at a dissolving temperature of 45° C., a dissolving stirring speed of 400-450 rpm, and a dissolving stirring time of 120 min to obtain a CS solution;
[0023] In the step 1, the preparation method of the APP solution is to dissolve APP in deionized water and stir to dissolve it at a dissolution temperature of 80° C., a dissolution stirring speed of 400-450 rpm, and a dissolution stirring time of 120 min to obtain an APP solution;
[0024] In the step 1, the dropping conditions are as follows: the dropping temperature is 45° C., the dropping stirring speed is 600-650 rpm, the dropping stirring time is 1 h, and the dropping acceleration rate is 0.5 drops / s;
[0025] Step 2, preparation of melamine-urea-formaldehyde resin emulsion MUF, first, adding sodium hydroxide solution to the formaldehyde solution to adjust the pH value of the solution to 8.0-8.5, then heating to 90° C. under a stirring speed of 400-450 rpm, and then adding raw materials in three stages to prepare melamine-urea-formaldehyde resin emulsion MUF, referred to as MUF,
[0026] In the step 2, the mass ratio of the total added amount of CLA, formaldehyde, melamine MEL and urea obtained in step 1 is 2:100:1.14:57;
[0027] In step 2, the ratio of urea added in the three stages is 37:12.4:7.6;
[0028] The three specific stages are:
[0029] Stage 2.1 is to add the first stage urea first and then add melamine MEL while maintaining the temperature at 90°C. After the addition is completed, stirring is continued for 30 minutes.
[0030] Stage 2.2 is to add lactic acid solution at 90°C, adjust the pH value of the solution to 4.5-5.0, and then add the second stage urea. After the addition is completed, continue stirring for 10 minutes until the reaction reaches the end point.
[0031] The judgment mark of the reaction end point of the stage 2.2 is that a drop of the solution is dropped into 30°C water, and the dropped solution condenses in the water without dispersing;
[0032] Stage 2.3 is to add sodium hydroxide solution at 90°C to adjust the pH value of the solution to 7.5-8.0, and then add urea in the third stage. After the addition is completed, adjust the temperature and stir at 70°C for 30 minutes to obtain MUF.
[0033] Step 3, preparation of bio-based flame retardant coating MUF / CLA based on ammonium polyphosphate, wherein MUF, dioctyl phthalate DOP, tannic acid TA and CLA obtained in step 1 meet a certain mass ratio, DOP, TA and CLA are added to MUF obtained in step 2, and after the addition is completed, mechanical stirring is performed under certain conditions to mix the components evenly, thereby obtaining bio-based flame retardant coating MUF / CLA based on ammonium polyphosphate, referred to as MUF / CLA;
[0034] In the step 3, the mass ratio of MUF, DOP, TA and CLA obtained in the step 1 is 100:1:1:2;
[0035] In step 3, the conditions for mechanical stirring are: a stirring speed of 600-650 rpm and a stirring time of 2 h.
[0036] Bio-based flame retardant coating based on ammonium polyphosphate, when used as wood flame retardant coating, has flame retardant properties and passes UL-94V-0 grade test; the residual carbon layer formed after complete combustion is continuous and dense; the limiting oxygen index is 32.6±0.06%; the maximum heat release rate is 42.83±1.51kW / m 2 The total heat release is 2.62±1.25MJ / m 2 , the fire growth index is 0.37±0.02kW / m 2 ·s.
[0037] The technical effects obtained by the present invention are as follows:
[0038] The TG test results show that when MUF / CLA is used as the bio-based flame retardant coating in the present invention, the temperature at which the MUF / CLA decomposes to 5% is 228.63°C, the temperature at which the maximum decomposition rate is reached is 295.4°C, and the residual carbon content at 800°C is 24.29wt.%. Coating MUF / CLA can increase the residual carbon content of the material and form a more stable carbon layer in the high temperature zone.
[0039] The expanded carbon layer formed on the surface of NW coated with MUF / CLA flame retardant coating after combustion was further tested by SEM. After MUF / CLA was completely burned, a complete and dense residual carbon layer was formed, and there was no expansion phenomenon. The test results show that the dense residual carbon layer of MUF / CLA can effectively isolate the release of combustible gas and heat, and improve the flame retardant properties of wood.
[0040] Through the vertical burning test and the limiting oxygen index test, it can be seen that W / MUF / CLA has passed the UL-94V-0 grade test.
[0041] Through the limiting oxygen index test, it can be seen that W / MUF / CLA flame retardant coating can improve its limiting oxygen index, LOI up to 32.6%.
[0042] The cone calorimetry test showed that the time to reach the maximum heat release rate was 113s, and the maximum heat release rate was 42.83kW / m 2 The total heat release is 2.62MJ / m 2 .
[0043] Therefore, the present invention has the following advantages over the prior art:
[0044] 1. The bio-based flame retardant CLA used in the present invention promotes the formation of a carbon layer, prevents the release of combustible gas and heat, and thus improves the flame retardant performance;
[0045] 2. The bio-based flame retardant CLA used in the present invention has a residual carbon content of less than 30% after thermal decomposition, but can still effectively inhibit combustion, thereby improving flame retardancy.
[0046] 3. The present invention uses renewable biomass materials lignin and chitosan, which are biodegradable and have low environmental impact. The combined use of ammonium polyphosphate and lignin can produce a synergistic effect and improve the flame retardant properties of the material. BRIEF DESCRIPTION OF THE DRAWINGS
[0047] Figure 1 is the FTIR graph of Example 1;
[0048] Figure 2 FTIR images of Example 1 and Comparative Example 1;
[0049] Figure 3 TG diagrams of Comparative Example 1, Comparative Example 2, Example 1, Example 2 and Comparative Example 3;
[0050] Figure 4 The SEM images of the carbon residue layer after combustion of the reference example, comparative example 1, comparative example 2, embodiment 1, embodiment 2 and comparative example 3 are shown in FIG. Figure 4 a is the reference ratio, Figure 4 b is comparative example 1, Figure 4 c is comparative example 2, Figure 4 d is the figure of Example 1, 4e is the figure of Example 2, Figure 4 f is comparative example 4;
[0051] Figure 5 It is a vertical combustion test diagram of reference example, comparative example 1, comparative example 2, embodiment 2, embodiment 1 and comparative example 3, wherein Figure 5 a is before vertical burning test, Figure 5 b is after vertical burning test;
[0052] Figure 6 Cone calorimetry test diagrams of reference example, comparative example 1, comparative example 2, example 2, example 1 and comparative example 3. DETAILED DESCRIPTION
[0053] The present invention is further described in detail through embodiments and in conjunction with the accompanying drawings, but the present invention is not limited thereto.
[0054] Example 1
[0055] A method for preparing a bio-based flame retardant coating based on ammonium polyphosphate comprises the following steps:
[0056] Step 1, preparation of chitosan / lignin / ammonium polyphosphate bio-based flame retardant CLA, first, lignin LS, chitosan CS and ammonium polyphosphate APP satisfying a mass ratio of 2:2:1, respectively preparing LS solution, CS solution and APP solution, then, under certain dropping conditions, dropping the LS solution into the CS solution for reaction to obtain a LS / CS mixed solution, finally, under the same dropping conditions, dropping the APP solution into the LS / CS mixed solution for reaction, and then obtaining chitosan / lignin / ammonium polyphosphate bio-based flame retardant CS / LS / APP, referred to as CLA;
[0057] The preparation method of the LS solution is as follows: under the conditions of a dissolution temperature of 30° C., a dissolution stirring speed of 400 rpm, and a dissolution stirring time of 30 min, 2.1 g of lignin LS is placed in 10 mL of deionized water for stirring and dissolving to obtain a LS solution;
[0058] The preparation method of the CS solution is as follows: 2.0 g of chitosan CS is dissolved in 20 mL of 3% lactic acid solution under the conditions of a dissolution temperature of 45° C., a dissolution stirring speed of 400 rpm, and a dissolution stirring time of 120 min, and the mixture is stirred and dissolved to obtain a CS solution;
[0059] The preparation method of the APP solution is as follows: under the conditions of a dissolution temperature of 80° C., a dissolution stirring speed of 400 rpm, and a dissolution stirring time of 120 min, 1.0 g of ammonium polyphosphate APP is dissolved in 10 mL of deionized water and stirred to dissolve, thereby obtaining an APP solution;
[0060] The dropping conditions are as follows: the dropping temperature is 45°C, the dropping stirring speed is 600 rpm, the dropping stirring time is 1 h, and the dropping acceleration rate is 0.5 drops / s;
[0061] In order to prove the composition of CLA, that is, the successful synthesis, FTIR test was carried out; at the same time, for comparison, the raw materials CS, LS and APP were subjected to FTIR test. The test results are as follows Figure 1 As shown,
[0062] CS has characteristic peaks of -OH and -NH2 functional groups;
[0063] LS has characteristic peaks of -OH and -NH2 functional groups;
[0064] APP has P=O and PO characteristic peaks;
[0065] CLA has the characteristic peak of -CONH2;
[0066] The test results show that the characteristic peak of -CONH2 in CLA is generated by the condensation reaction of the amino group of chitosan and the phenolic hydroxyl group of lignin under acidic heating conditions to form amide.
[0067] Step 2, preparation of melamine-urea-formaldehyde resin emulsion MUF, first, add 20wt.% sodium hydroxide solution to 100g 37wt.% formaldehyde solution, adjust the pH value of the solution to 8.0-8.5, then heat to 90°C under stirring speed of 400rpm, then add raw materials in 3 stages to prepare melamine-urea-formaldehyde resin emulsion MUF, referred to as MUF,
[0068] The three specific stages are:
[0069] Stage 2.1 is to add 37g of the first stage urea and then 1.14g of melamine MEL while maintaining the temperature at 90°C. After the addition is completed, stirring is continued for 30 minutes.
[0070] Stage 2.2 is to add 10 wt.% lactic acid solution at 90°C, adjust the pH value of the solution to 4.5-5.0, and then add 12.4 g of the second stage urea. After the addition is completed, continue stirring for 10 minutes until the reaction reaches the end point;
[0071] The judgment mark of the reaction end point of the stage 2.2 is that a drop of the solution is dropped into 30°C water, and the dropped solution condenses in the water without dispersing;
[0072] Stage 2.3 is to add 20wt.% sodium hydroxide solution while maintaining the temperature at 90°C, adjust the solution pH to 7.5-8.0, and then add 7.6g of the third stage urea. After the addition is completed, adjust the temperature and stir at a stirring temperature of 70°C for 30 minutes to obtain MUF.
[0073] Step 3, preparation of ammonium polyphosphate-based bio-based flame retardant coating MUF / CLA, with a mass ratio of MUF, dioctyl phthalate DOP, tannic acid TA and CLA obtained in step 1 being 100:1:1:2, 1g DOP, 1g TA and 2g CLA are added to the MUF obtained in step 2. After the addition is completed, mechanical stirring is performed at a stirring speed of 600rpm and a stirring time of 2h to mix the components evenly, and the ammonium polyphosphate-based bio-based flame retardant coating MUF / CLA can be obtained, which is referred to as MUF / CLA. The MUF / CLA obtained in specific example 1 is MUF / CLA-2.
[0074] In order to prove the composition of MUF / CLA-2, FTIR test was performed. The test results are as follows Figure 2As shown, MUF / CLA-2 has characteristic peaks of -OH, -NH2, P=O, PO and -CONH2, as well as characteristic peaks of -CHO. The test results show that MUF and CLA are the main components in MUF / CLA-1.
[0075] In order to prove the thermal stability of MUF / CLA-2, TG test was carried out. The test results are shown in Figure 3 As shown in Table 1, the temperature at which MUF / CLA-2 decomposes to 5% by mass is 228.63°C, the temperature at which the maximum decomposition rate is reached is 295.4°C, and the residual carbon content at 800°C is 24.29wt.%. The test results show that MUF / CLA-2 has high thermal stability and a high residual carbon content.
[0076] Table 1 Thermogravimetric test results
[0077]
[0078] In order to prove the technical effect of MUF / CLA-2 as a wood flame retardant coating, MUF / CLA-2 was coated on the wood surface to prepare flame retardant wood W / MUF / CLA-2 for flame retardant test. The specific preparation method of W / MUF / CLA-2 is as follows: the coating thickness is 0.3mm and the coating density is 0.1g / cm 2 MUF / CLA-2 is coated on the wood surface. After coating, it is dried for 24 hours to obtain W / MUF / CLA-2.
[0079] In order to prove the quality of the carbon residue layer of MUF / CLA-2, SEM test was carried out on the carbon residue layer after the complete combustion of MUF / CLA-2. Figure 4 As shown in Figure c, the flame-retardant wood coated with MUF / CLA-2 forms a complete and dense residual carbon layer after complete combustion, and there is no expansion phenomenon. The test results show that the dense residual carbon layer of MUF / CLA-2 can effectively isolate the release of combustible gas and heat, and improve the flame retardant performance of wood.
[0080] In order to further prove the flame retardant performance of W / MUF / CLA-2, vertical burning test and limiting oxygen index test were carried out. Figure 5 As shown in Table 2, W / MUF / CLA-2 passed the UL-94V-0 grade test; and the limiting oxygen index of W / MUF / CLA-2 was as high as 32.6%. The test results show that W / MUF / CLA-2 has excellent flame retardant properties.
[0081] Table 2 Vertical combustion test and oxygen index test results
[0082]
[0083] In order to further prove the flame retardant performance of W / MUF / CLA-2 under real combustion conditions, cone calorimetry test was carried out. Figure 6 As shown in Table 3, the time to reach the maximum heat release rate of W / MUF / CLA-2 is 113s, and the maximum heat release rate is 42.83kW / m 2 The total heat release is 2.62MJ / m 2 , the fire growth index is 0.37kW / m 2 ·s. The test results show that W / MUF / CLA-2 has excellent flame retardant properties.
[0084] Table 3 Cone calorimetry test results
[0085]
[0086] In order to demonstrate the effect of bio-based flame retardant CLA on performance, comparative example 1 is provided, which is a flame retardant coating without adding bio-based flame retardant CLA; at the same time, a reference example is provided, which is pure wood without any coating as a basic reference.
[0087] Reference ratio
[0088] A type of wood that is not coated with MUF / CLA, referred to as pure wood.
[0089] The SEM test results of the residual carbon layer of pure wood are as follows Figure 4 As shown in a, the carbon layer structure in the pure wood is completely destroyed, and a large number of broken cellulose and hemicellulose structures are clearly visible. After burning and breaking, there are neatly arranged pore structures inside the pure wood. Compared with Example 1, it can be seen that the coating of MUF / CLA-1 makes the expanded carbon residue layer generated on the wood surface form a complete and dense carbon residue layer, and there is no expansion phenomenon. That is, the quality of the carbon residue layer is greatly improved.
[0090] The results of the vertical combustion test and limiting oxygen index test of pure wood are as follows: Figure 5 As shown in Table 2, pure wood does not pass the UL-94 grade test; and the limiting oxygen index of pure wood is 20.0%. Compared with Example 1, coating MUF / CLA-1 can improve the UL-94 grade to V-0, and the limiting oxygen index is greatly increased from 20.0% to 32.5%, an increase of 62.5%. The test results show that MUF / CLA-1 can significantly improve the flame retardant properties of pure wood.
[0091] The cone calorimetry test results of pure wood are as follows Figure 6 As shown in Table 3, the maximum heat release rate of pure wood is 138s, the maximum heat release rate is 212.49kW / m2, and the total heat release is 11.35MJ / m 2The fire growth index is 1.54kW / m 2 ·s. Compared with Example 1, coating MUF / CLA-2 shortens the time for flame-retardant wood to reach the maximum heat release rate by 25s, reduces the maximum heat release rate by 79.84%, reduces the total heat release by 76.91%, and reduces the fire growth index by 75.97%. The test results show that MUF / CLA-2 can significantly improve flame retardancy and significantly reduce fire hazards.
[0092] Comparative Example 1
[0093] A conventional coating without adding a bio-based flame retardant CLA, that is, a method for preparing a conventional coating, wherein the steps not specifically stated are the same as those in Example 1, except that: in the step 3, the bio-based flame retardant CLA is not added, the obtained conventional coating is named MUF, and the obtained conventional flame-retardant wood is named W / MUF.
[0094] The TG test results of MUF are as follows: Figure 3 As shown in Table 1, the temperature at which the MUF decomposition mass was 5% was 190.79°C, the temperature at which the maximum decomposition rate was reached was 301.3°C, and the residual carbon content at 800°C was 12.5 wt.%.
[0095] Compared with Example 1, it can be seen that the addition of the bio-based flame retardant CLA can significantly increase the temperature when the decomposition mass is 5% and significantly increase the amount of residual carbon at 800°C. The increase in the temperature when the decomposition mass is 5% is 37.84°C, and the increase in the amount of residual carbon at 800°C is 11.79wt.%. However, the temperature at which the maximum decomposition rate is reached is reduced by 5.9°C. Therefore, the test results show that the addition of APP can significantly improve the flame retardant properties.
[0096] The SEM test results of the residual carbon layer of W / MUF are as follows Figure 4 As shown in b, a large number of bubbles of different sizes are formed on the surface of the residual carbon layer formed after the complete combustion of W / MUF.
[0097] Compared with reference example 1, although the conventional coating MUF can form an expanded carbon layer on the wood surface, there are many holes on the surface of the residual carbon layer, which cannot effectively protect the wood, which proves that MUF has no substantial effect on the quality of the residual carbon layer.
[0098] Compared with Example 1, the addition of the bio-based flame retardant CLA can transform the existing porous carbon residue layer into a continuous and dense carbon residue layer without the presence of holes, which means that the morphology and structure of the carbon residue layer can be significantly changed.
[0099] The test results show that the use of bio-based flame retardant CLA can improve the quality of the expanded carbon residue layer of W / MUF / CLA, thereby improving the flame retardant performance.
[0100] W / MUF vertical combustion test and limiting oxygen index test results are as follows Figure 5 As shown in Table 2, W / MUF passed the UL-94V-1 grade test; and, the limiting oxygen index of W / MUF was 29.0%.
[0101] Compared with reference example 1, it can be seen that applying conventional coating MUF can only improve the UL-94 grade of wood from failing the test to V-1 grade, but cannot reach V-0 grade. At the same time, it can increase the limiting oxygen index by 9.0%;
[0102] Compared with Example 1, the use of bio-based flame retardant CLA can further improve the UL-94 grade of flame-retardant wood from V-1 to V-0, and can further increase the limiting oxygen index by 3.5%.
[0103] Test results show that the use of bio-based flame retardant CLA can improve the UL-94 rating and significantly increase the limiting oxygen index, thereby significantly improving flame retardant properties.
[0104] The cone calorimetry test results of W / MUF are shown in Figure 6 As shown in Table 3, the maximum heat release rate of W / MUF is 113s, the maximum heat release rate is 60.56kW / m2, and the total heat release is 4.47MJ / m 2 , the fire growth index is 0.53kW / m 2 ·s.
[0105] Compared with reference example 1, the use of conventional coating MUF can shorten the time for flame-retardant wood to reach the maximum heat release rate by 25s, reduce the maximum heat release rate by 71.49%, reduce the total heat release by 60.61%, and reduce the fire growth index by 65.58%.
[0106] Compared with Example 1, the use of conventional coating MUF can shorten the time for flame-retardant wood to reach the maximum heat release rate by 25s, reduce the maximum heat release rate by 29.27%, reduce the total heat release by 41.38%, and reduce the fire growth index by 30.18%.
[0107] The test results show that the use of bio-based flame retardant CLA can greatly improve the flame retardant properties of flame-retardant wood in real burning conditions and significantly reduce the fire hazard.
[0108] In order to further demonstrate the influence of each component in the bio-based flame retardant CLA on the performance, that is, the role of APP in the technical solution, Comparative Example 2 is provided, which is a bio-based flame retardant and flame retardant coating prepared without adding APP.
[0109] Comparative Example 2
[0110] A method for preparing a bio-based flame retardant coating CL without adding APP, wherein the steps not specifically stated are the same as those in Example 1, except that: in step 3, APP is not added, the bio-based flame retardant obtained in step 1 is named CL, the flame retardant coating obtained in step 3 is named MUF / CL, and the flame retardant wood obtained is further named W / MUF / CL.
[0111] The TG test results of MUF / CL are as follows: Figure 3 As shown in Table 1, the temperature at which the MUF / CL decomposition mass was 5% was 183.9°C, the temperature at which the maximum decomposition rate was reached was 301.3°C, and the residual carbon content at 800°C was 12.0 wt.%.
[0112] Compared with Comparative Example 1, although the addition of CL can slightly increase the temperature at which the maximum decomposition rate is reached, by only 1.8°C, it can also reduce the temperature and residual carbon content at a decomposition mass of 5%, by 6.89°C and 0.5wt.%, respectively. Therefore, the test results show that the addition of CL alone can lead to a decrease in the flame retardancy of MUF.
[0113] Compared with Example 1, although the addition of APP will cause the temperature at the maximum decomposition rate to decrease by 7.9°C, it can significantly increase the temperature and residual carbon content when the decomposition mass is 5%. The increase in temperature when the decomposition mass is 5% reaches 44.73°C, and the increase in residual carbon content is 12.19wt.%, and the increase is 102.41%. Therefore, the test results show that the addition of APP can significantly improve the flame retardant properties.
[0114] The SEM test results of the residual carbon layer of W / MUF / CL are as follows Figure 4 As shown in Figure c, after the complete combustion of W / MUF / CL, although a continuous residual carbon layer can be formed, there are still holes on the surface of the residual carbon layer, and there are expanded bubbles, which is the expanded carbon layer.
[0115] Compared with reference example 1, although coating MUF / CL can form a continuous carbon residue layer on the wood surface, there are expanded bubbles and holes on the surface of the carbon residue layer, which cannot effectively protect the wood, which proves that MUF / CL has no substantial effect on the quality of the carbon residue layer.
[0116] Compared with Comparative Example 1, it can be seen that the addition of CL can slightly reduce the phenomenon of expansion bubbles and holes in the residual carbon layer, that is, slightly improve the flame retardancy, but there is no substantial change in the residual carbon layer formed with MUF, which proves that CL has no substantial effect on the quality of the residual carbon layer;
[0117] Compared with Example 1, it can be seen that the addition of APP can significantly change the morphology and structure of the residual carbon layer, transforming the original cracks and holes into a dense state, and there is no expansion phenomenon;
[0118] The test results show that the addition of bio-based flame retardant APP can significantly change the morphology and structure of the residual carbon layer. The reason is that APP is dehydrated under high temperature conditions to generate polyphosphoric acid or metaphosphoric acid, which then undergoes a dehydration reaction with the hydroxyl groups in CL to form a complete and dense carbon layer, thereby improving the quality of the expanded residual carbon layer of W / MUF / CL and thus improving the flame retardant properties.
[0119] W / MUF / CL vertical combustion test and limiting oxygen index test results are as follows Figure 5 As shown in Table 2, W / MUF / CL passed the UL-94V-1 grade test, and the limiting oxygen index of W / MUF / CL was 29.5%.
[0120] Compared with reference example 1, coating MUF / CL can only improve the UL-94 grade of wood from failing the test to V-1 grade, but cannot reach V-0 grade. At the same time, it can increase the limiting oxygen index by 9.5%.
[0121] Compared with Comparative Example 1, it can be seen that the addition of CL has no substantial effect on the UL-94 grade, which is still V-1 grade, and has no substantial effect on the limiting oxygen index, which is only increased by 0.5%, indicating that the addition of CL has no substantial effect on the flame retardant properties;
[0122] Compared with Example 1, it can be seen that the addition of the bio-based flame retardant APP can improve the UL-94 grade of the flame-retardant wood from V-1 to V-0, and can further significantly increase the limiting oxygen index by 3.1%.
[0123] The test results show that adding CL alone has no substantial effect on the flame retardant properties. Only when APP is added at the same time can it have a substantial impact on the UL-94 grade and the limiting oxygen index. This proves that the role of APP in the technical solution is reflected in that it can significantly improve the flame retardant properties.
[0124] Cone calorimetry test results of W / MUF / CL are shown in Figure 6 As shown in Table 3, the time to reach the maximum heat release rate of W / MUF / CL is 96s, and the maximum heat release rate is 57.6kW / m 2 The total heat release is 5.15MJ / m 2 , the fire growth index is 0.6kW / m 2 ·s.
[0125] Compared with reference example 1, coating MUF / CL can shorten the time for flame-retardant wood to reach the maximum heat release rate by 38s, significantly reduce the maximum heat release rate by 64.05%, the total heat release by 60.44%, and the fire growth index by 50.64%.
[0126] Compared with Comparative Example 1, adding CL can shorten the time for flame-retardant wood to reach the maximum heat release rate by 17s, increase the maximum heat release rate by 4.88%, increase the total heat release by 15.2%, and increase the fire growth index by 13.2%. That is, adding CL has no substantial effect on the flame retardant performance in real combustion conditions.
[0127] Compared with Example 1, although the addition of APP increases the time for the flame-retardant wood to reach the maximum heat release rate by 17s, it can reduce the maximum heat release rate by 25.64%, the total heat release by 49.12%, and the fire growth index by 38.33%.
[0128] The test results show that adding the bio-based flame retardant CLA can significantly improve the flame retardant properties of wood in real burning conditions and significantly reduce the risk of fire.
[0129] In order to demonstrate the effect of CLA addition on performance, comparative examples 3 and 4 are provided, in which CLA addition amounts are 1 wt.% and 3 wt.% of the total MUF, respectively, referred to as flame retardant coatings prepared with CLA addition amounts of 2 wt.% and 3 wt.%.
[0130] Example 2
[0131] A method for preparing MUF / CLA with a CLA addition amount of 1 wt.%, wherein the steps not specifically specified are the same as those of Example 1, except that: in step 3, the CLA addition amount is 1 wt.%, specifically, 1 g CLA is added, and the resulting flame retardant coating is named MUF / CLA-1, and the resulting flame retardant wood is further named W / MUF / CLA-1.
[0132] The TG test results of MUF / CLA-1 are as follows: Figure 3 As shown in Table 1, the temperature at which MUF / CLA-1 decomposes to 5% by weight is 235.64°C, the temperature at which the maximum decomposition rate is reached is 281.5°C, and the amount of residual carbon at 800°C is 19.64 wt.%.
[0133] Compared with Comparative Example 1, adding a small amount of CLA can also significantly increase the temperature at 5% decomposition mass by 44.85°C, increase the temperature at the maximum mass loss rate by 19.8°C, and increase the residual carbon content by 7.14wt.%. Therefore, the test results show that even adding a small amount of CLA can significantly improve the thermal stability and residual carbon content.
[0134] Compared with Example 1, increasing the amount of CLA added can increase the temperature at 5% decomposition by 7.01°C, but the temperature at the maximum mass loss rate decreases by 13.9°C, and the amount of residual carbon at 800°C decreases by 4.06wt.%.
[0135] Therefore, the test results show that increasing the addition amount of CLA can improve the thermal stability and carbon residue.
[0136] The SEM test results of the residual carbon layer of MUF / CLA-1 are as follows: Figure 4 As shown in Figure e, after the complete combustion of W / MUF / CLA-1, a complete and dense residual carbon layer is formed.
[0137] Compared with reference example 1, it can be seen that adding a small amount of CLA can also transform the original porous carbon residue layer into a continuous and dense carbon residue layer, that is, significantly improve the quality of the carbon residue layer.
[0138] Compared with Comparative Example 1, it can be seen that adding a small amount of CLA can also transform the residual carbon layer with bubbles into a continuous and dense residual carbon layer;
[0139] Compared with Example 1, it can be seen that increasing the amount of CLA added has no substantial effect on the residual carbon layer, that is, it still remains continuous and dense.
[0140] The test results show that within the addition range, the addition amount of CLA has no substantial effect on the quality of the residual carbon layer.
[0141] The vertical combustion test and limiting oxygen index test results of W / MUF / CLA-1 are as follows Figure 5 As shown in Table 2, in the vertical burning test, the UL-94 V-0 grade test was passed; and the limiting oxygen index of W / MUF / CLA-1 was 31.5%.
[0142] Compared with reference example 1, adding a small amount of CLA can also improve the UL-94 grade of wood from failing the test to V-0 grade, and at the same time, can significantly increase the limiting oxygen index by 11.5%;
[0143] Compared with Comparative Example 1, it can be seen that adding a small amount of CLA can also improve the UL-94 grade of wood from V-1 to V-0, and at the same time, can increase the limiting oxygen index by 2.5%.
[0144] Compared with Example 1, it can be seen that increasing the amount of CLA added cannot change the UL-94 grade of the flame retardant wood, but can increase the limiting oxygen index by 1.1%.
[0145] W / MUF / CLA-1 cone calorimetry test results are as follows Figure 6As shown in Table 3, the maximum heat release rate of W / MUF / CLA-1 is 100s, and the maximum heat release rate is 44.72kW / m 2 , the total heat release is 2.35MJ / m 2 The fire growth index is 0.44kW / m 2 ·s.
[0146] Compared with reference example 1, adding a small amount of CLA can also shorten the time for flame-retardant wood to reach the maximum heat release rate by 38s, significantly reduce the maximum heat release rate by 78.95%, the total heat release by 79.29%, and the fire growth index by 71.42%.
[0147] Compared with comparative example 1, adding a small amount of CLA can also shorten the time for flame-retardant wood to reach the maximum heat release rate by 13s, reduce the maximum heat release rate by 26.15%, reduce the total heat release by 47.42%, and reduce the fire growth index by 16.98%.
[0148] Compared with Example 1, increasing the amount of CLA added can reduce the time for the flame-retardant wood to reach the maximum heat release rate by 13s, reduce the total heat release by 10.30%, and increase the fire growth index by 18.91%, but increase the maximum heat release rate by 4.41%.
[0149] The test results show that increasing the amount of CLA added can further improve the flame retardant properties of wood in real burning conditions.
[0150] Comparative Example 3
[0151] A method for preparing MUF / CLA with a CLA addition amount of 3 g, wherein the steps are the same as those in Example 1 unless otherwise specified, except that in step 3, the CLA addition amount is 3 wt.%, specifically, 3 g CLA is added, and the resulting flame retardant coating is named MUF / CLA-3, and the resulting flame retardant wood is further named W / MUF / CLA-3.
[0152] The TG test results of MUF / CLA-3 are as follows: Figure 3 As shown in Table 1, the temperature at which the decomposition mass of MUF / CLA-3 was 5% was 211.74°C, the temperature at which the maximum decomposition rate was reached was 307.1°C, and the residual carbon content at 800°C was 22.71 wt.%.
[0153] Compared with Comparative Example 1, it can be seen that adding excessive CLA can also increase the temperature at 5% decomposition mass by 20.95°C, increase the temperature at the maximum mass loss rate by 5.8°C, and increase the residual carbon content by 10.21wt.%. Therefore, the test results show that adding excessive CLA can improve thermal stability and residual carbon content.
[0154] Compared with Example 1, although the addition of excessive CLA can further increase the temperature at the maximum mass loss rate by 11.7°C, it significantly reduces the temperature at 5% decomposition mass and the amount of residual carbon at 800°C. The temperature at 5% decomposition mass decreases by 16.89°C, and the amount of residual carbon at 800°C decreases by 1.58wt.%. Therefore, the test results show that the addition of excessive CLA not only fails to further improve the flame retardant properties, but reduces the flame retardant properties.
[0155] The SEM test results of the residual carbon layer of W / MUF / CLA-3 are as follows Figure 4 As shown in Fig. f, after the complete combustion of W / MUF / CLA-3, a continuous carbon residue layer can be formed, but there are still holes on the surface of the carbon residue layer.
[0156] Compared with Reference Example 1, it can be seen that adding excessive CLA can form a continuous carbon residue layer on the wood surface, but cracks appear on the surface and a large number of holes of different sizes are formed, which proves that adding excessive CLA can still improve the quality of the carbon residue layer;
[0157] Compared with Comparative Example 1, it can be seen that adding excessive CLA can also reduce the expansion bubble phenomenon of the residual carbon layer and improve the flame retardant performance;
[0158] Compared with Example 1, it can be seen that the addition of excessive CLA forms holes of different sizes on the continuous and dense carbon residue layer;
[0159] The test results show that adding excessive CLA will produce new defects after combustion, causing a porous structure in the dense residual carbon layer, resulting in a decrease in flame retardant properties.
[0160] The vertical combustion test and limiting oxygen index test results of W / MUF / CLA-3 are as follows: Figure 5 As shown in Table 2, in the vertical burning test, the UL-94V-1 grade test was passed, and the limiting oxygen index was 30.0%.
[0161] Compared with reference example 1, it can be seen that adding excessive CLA can improve the UL-94 grade of wood from failing the test to V-1 grade, and at the same time, it can significantly increase the limiting oxygen index by 10.0%;
[0162] Compared with Comparative Example 1, it can be seen that adding excessive CLA cannot improve the UL-94 rating of the flame retardant wood, but can increase the limiting oxygen index by 1.0%.
[0163] Compared with Example 1, it can be seen that adding excessive CLA can reduce the UL-94 grade of the flame retardant wood from V-0 to V-0, and reduce the limiting oxygen index by 2.6%.
[0164] Further comparison with Example 2 shows that although adding excessive CLA can improve the limiting oxygen index, the UL-94 grade decreases. Combined with the SEM test results, it shows that adding an appropriate amount of CLA can form a continuous and dense residual carbon layer, that is, a high-quality residual carbon layer, and it can also be proved that the limiting oxygen index is not the only criterion for judging flame retardancy.
[0165] W / MUF / CLA-3 cone calorimetry test results are as follows Figure 6 As shown in Table 3, the maximum heat release rate of W / MUF / CLA-3 is 82s, and the maximum heat release rate is 55.04kW / m 2 , the total heat release is 3.42m 2 , the fire growth index is 0.67kW / m 2 ·s.
[0166] Compared with reference example 1, adding excessive CLA shortens the time for flame-retardant wood to reach the maximum heat release rate by 56, significantly reduces the maximum heat release rate by 74.09%, reduces the total heat release by 69.86%, and reduces the fire growth index by 56.49%.
[0167] Compared with Comparative Example 1, it can be seen that the addition of excessive CLA shortens the time for the flame-retardant wood to reach the maximum heat release rate by 31s, reduces the maximum heat release rate by 9.11%, reduces the total heat release by 23.48%, and increases the fire growth index by 26.41%. That is, the addition of MUF / CLA-3 can slightly improve the flame retardant performance of wood in real combustion conditions, but increases the fire growth index.
[0168] Compared with Example 1, although the addition of excessive CLA reduces the time for the flame-retardant wood to reach the maximum heat release rate by 31s, increases the total heat release by 30.53%, and increases the fire growth index by 81.08%, the maximum heat release rate increases by 12.21%.
[0169] The test results show that adding excessive CLA can improve the flame retardant properties of wood in real combustion conditions, but it increases the maximum heat release rate, that is, the amount of CLA added cannot be too much.
[0170] By comparing Example 1, Example 2 and Comparative Example 3, it can be seen that:
[0171] 1. The flame retardant properties of wood coated with MUF / CLA are greatly improved compared with uncoated pure wood. The flame retardant coating can effectively improve the flammable properties of wood and make the wood flame retardant;
[0172] 2. Adding an appropriate amount of CLA as a bio-based flame retardant can effectively improve the thermal stability, limiting oxygen index, UL-94 grade and flame retardant properties of W / MUF. As its content increases, the thermal stability of W / MUF increases accordingly; however, adding excessive CLA will lead to a decrease in residual carbon content, limiting oxygen index and UL-94 grade.
Claims
1. A bio-based flame retardant coating based on ammonium polyphosphate, characterized in that: The invention adopts chitosan / lignin / ammonium polyphosphate bio-based flame retardant CS / LS / APP, abbreviated as CLA, as flame retardant, urea, formaldehyde and melamine as resin raw materials, dioctyl phthalate DOP as plasticizer, and tannic acid as curing agent; the CLA is prepared from lignin LS, chitosan CS and ammonium polyphosphate APP, and CLA contains -NH2, OH, P=O, PO - 、-CONH2.
2. The bio-based flame retardant coating based on ammonium polyphosphate according to claim 1, characterized in that: The temperature at which the decomposition mass of the obtained CLA reached 5% was 228.63±5°C, and the temperature at which the maximum decomposition rate was reached was 295.4±5°C; the residual carbon content at 800°C was 24.29±2wt.%.
3. A method for preparing a bio-based flame retardant coating based on ammonium polyphosphate, characterized in that The following steps are involved: Step 1, preparation of chitosan / lignin / ammonium polyphosphate bio-based flame retardant CLA, first, lignin LS, chitosan CS and ammonium polyphosphate APP meet a certain mass ratio, prepare LS solution, CS solution and APP solution respectively, then, under certain dropping conditions, add the LS solution dropwise into the CS solution to react to obtain a LS / CS mixed solution, finally, under the same dropping conditions, add the APP solution dropwise into the LS / CS mixed solution to react, and obtain chitosan / lignin / ammonium polyphosphate bio-based flame retardant CS / LS / APP, referred to as CLA; Step 2, preparation of melamine-urea-formaldehyde resin emulsion MUF, first, adding sodium hydroxide solution to the formaldehyde solution to adjust the pH value of the solution to 8.0-8.5, then heating to 90° C. under a stirring speed of 400-450 rpm, and then adding raw materials in three stages to prepare melamine-urea-formaldehyde resin emulsion MUF, referred to as MUF, Step 3, preparation of ammonium polyphosphate-based bio-based flame retardant coating MUF / CLA, with MUF, dioctyl phthalate DOP, tannic acid TA and CLA obtained in step 1 satisfying a certain mass ratio, adding DOP, TA and CLA to the MUF obtained in step 2, after the addition is completed, mechanical stirring is performed under certain conditions to mix the components evenly, and the ammonium polyphosphate-based bio-based flame retardant coating MUF / CLA, referred to as MUF / CLA, can be obtained.
4. The preparation method according to claim 3, characterized in that: In the step 1, the mass ratio of LS, CS and APP is 2:2:
1.
5. The preparation method according to claim 3, characterized in that: In the step 1, the preparation method of the LS solution is to place LS in deionized water for stirring and dissolving at a dissolving temperature of 30° C., a dissolving stirring speed of 400-450 rpm, and a dissolving stirring time of 30 min to obtain a LS solution; In the step 1, the CS solution is prepared by dissolving CS in a lactic acid solution and stirring and dissolving the CS solution at a dissolving temperature of 45° C., a dissolving stirring speed of 400-450 rpm, and a dissolving stirring time of 120 min to obtain a CS solution; In the step 1, the preparation method of the APP solution is to dissolve APP in deionized water and stir to dissolve it at a dissolution temperature of 80° C., a dissolution stirring speed of 400-450 rpm, and a dissolution stirring time of 120 min to obtain an APP solution; In the step 1, the dropping conditions are as follows: the dropping temperature is 45° C., the dropping stirring speed is 600-650 rpm, the dropping stirring time is 1 h, and the dropping acceleration rate is 0.5 drops / s.
6. The preparation method according to claim 3, characterized in that: In the step 2, the mass ratio of the total added amount of CLA, formaldehyde, melamine MEL and urea obtained in step 1 is 2:100:1.14:57; In step 2, the ratio of urea added in three stages is 37:12.4:7.
6.
7. The preparation method according to claim 3, characterized in that: In step 2, the three stages are: Stage 2.1 is to add the first stage urea first and then add melamine MEL while maintaining the temperature at 90°C. After the addition is completed, stirring is continued for 30 minutes. Stage 2.2 is to add lactic acid solution at 90°C, adjust the pH value of the solution to 4.5-5.0, and then add the second stage urea. After the addition is completed, continue stirring for 10 minutes until the reaction reaches the end point. The judgment mark of the reaction end point of the stage 2.2 is that a drop of the solution is dropped into 30°C water, and the dropped solution condenses in the water without dispersing; Stage 2.3 is to add sodium hydroxide solution at 90°C to adjust the pH value of the solution to 7.5-8.0, and then add urea in the third stage. After the addition is completed, adjust the temperature and stir at 70°C for 30 minutes to obtain MUF.
8. The preparation method according to claim 3, characterized in that: In the step 3, the mass ratio of MUF, DOP, TA and CLA obtained in the step 1 is 100:1:1:2; In step 3, the conditions for mechanical stirring are: a stirring speed of 600-650 rpm and a stirring time of 2 h.
9. The bio-based flame retardant coating based on ammonium polyphosphate according to claim 1, characterized in that: When used as a flame retardant coating for wood, it has flame retardant properties and passes the UL-94V-0 grade test; the residual carbon layer formed after complete combustion is continuous and dense.
10. The bio-based flame retardant coating based on ammonium polyphosphate according to claim 1, characterized in that: When used as a wood flame retardant coating, the limiting oxygen index is 32.6±0.06%; the maximum heat release rate is 42.83±1.51kW / m 2 The total heat release is 2.62±1.25MJ / m 2 , the fire growth index is 0.37±0.02kW / m 2 ·s.
Citation Information
Patent Citations
Biomass flame retardant, water-based flame-retardant coating as well as preparation method and application of water-based flame-retardant coating
CN113493624A
Biomass expansive three-source integrated flame retardant as well as preparation method and application thereof
CN115124767A
Core-shell structure flame retardant as well as preparation method and application thereof
CN115819846A
PCS-based flame-retardant urea-formaldehyde resin as well as preparation method and application thereof
CN118374122A
Urea-formaldehyde resin blended guanazole-phytic acid-copper flame-retardant resin coating as well as preparation method and application thereof
CN119101427A
Cited By
Flame-retardant composite coating based on P-N-Si-Ca as well as preparation method and application of flame-retardant composite coating
CN121108837A